Editorial (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Writing is an indispensable part of research culture, and publication is one way to disseminate ideas and to push forward the scientific discourse in the pursuit of new knowledge, from theoretical- to praxis- levels. Especially for young scholars, writing and publishing in academic journals shall become a natural habit, not just for chasing credit points or impact factors, but for strengthening the true desire in finding new knowledge, ethically and scientifically.There are four different categories of articles in this issue. First category is on the correlation between ecological-environmental aspects and tourism in rural-traditional contexts, where the writers have shown their critical position towards cultural & natural conservation. Second category is on architectural styles and typology which are more descriptive. Third category is related to the climatic comfort and simulation. And the fourth category is on human activities in urban space.The article by Anna Pudianti and Vincentia Reni Vitasurya is looking into the ecological footprints in relation to village tourism in Yogyakarta from the anthropological perspective. Similar interest to village tourism and cultural-environmental conservation in Nias is shared by Anugerah Septiaman Harefa. Likewise, Rachmat Budihardjo is looking into the impact of tourism to the typological adaptation of the traditional architecture in Bali.Dessy Anggaini and Dwita Hadi Rahmi wrote about “Indisch-style” based on typological inventory in Yogyakarta. Anneke Clauvinia Patriajaya and Yohanes Karyadi Kusliansjah are lamenting on the transformation of urban street character in Surabaya. Tine Abrianti and Purnama Salura wrote the sacred poetic of religious architecture in Jakarta.Rivena Elbes and Ai Siti Munawaroh article is on thermal comfort study on a library building in Lampung. Leonardus Murialdo Fransiskus Purwanto presented his analysis on heat transfer by a thermal simulation software.Finally, Raden Rangga Ilham Irfandian and Herman Wilianto presented their study on lifestyle aspect in urban public space in Bandung.This journal edition demonstrates the diversity of interests and approaches among young scholars. Although the level of criticality and the level of theoretical discourse can still be improved further, but these articles have shown a good promise for a higher level of scholarly pursuits.
Keywords: ARTEKS; December 2019; Indonesian Journal of Architecture; Issue 1; Volume 4